Biotratamiento de residuos cianurados y su relación con la salud pública (2010)
ABSTRACT: To propose a bio-treatment for cyanide residues generated by medico-legal procedures and to identify risk factors from handling. Methodology: cyanide residues, from the Institute of Legal Medicine, Medellin, were characterized by their physical state and identified its management, and risk factors. For the residues degradation 22 pre-essays and 9 bioassays were done with Pseudomonas aeruginosa and Thiobacillus ferrooxidans at different cyanide concentrations. Results: there were failures in all risk factors analyzed, predominating the chemical component which sources of pollution. In studies of degradation, Pseudomonas aeruginosa showed a 87% removal percentage at a concentration of 50 mg / L and Thiobacillus ferrooxidans, 79% removal at a concentration of 500 mg / L. We conducted a technical guide for the management of cyanide residues. Conclusions: The evaluation of the routes of cyanide from seizure to final disposal, were found that the Institute of Forensic Medicine had no documented guidelines on the management of them. Biological treatment with bacteria such as Pseudomonas aeruginosa and Thiobacillus ferrooxidans were efficient in the degradation of cyanide.